Novel clinical scoring system to identify patients with pneumothorax with suspicion for Birt–Hogg–Dubé syndrome. Issue 4 (27th September 2017) - Ebana, Hiroki; Mizobuchi, Teruaki; Kurihara, Masatoshi; Kobayashi, Etsuko; Haga, Takahiro; Okamoto, Shoichi; Takahashi, Kazuhisa; Seyama, Kuniaki
ABSTRACT: Background and objective: Birt–Hogg–Dubé syndrome (BHDS) is a rare hereditary disease that presents with multiple lung cysts and pneumothorax (PTX). Although some reports propose that findings from chest computed tomography enable one to distinguish BHDS from primary spontaneous pneumothorax (PSP), it is still unclear whether clinical features are useful for identifying patients with suspicion of BHDS from those with PTX. Methods: We retrospectively reviewed the medical records of patients with PTX who underwent video‐assisted thoracoscopic surgery at Nissan Tamagawa Hospital from January 2012 to December 2015. Results: We identified a total of 1141 patients with PTX, including 54 with BHDS and 517 with PSP. Among them, logistic regression analysis segregated five features that were significantly associated with BHDS: familial history of PTX, past history of bilateral PTX, age at the first episode of PTX (≥25 years old (y.o.)), body mass index (≥18.5) and gender (female). We assigned scores of 3, 3, 2, 2 and 1 to the five features, respectively, to establish a system with a calculated score from 0 to 11. The cut‐off value of a calculated score ≥ 4 yielded the highest sensitivity of 93% and specificity of 86%. Receiver operating characteristic (ROC) analysis showed the area under the curve reflecting an accuracy of this diagnostic test as 0.953. Conclusion: BHDS has several clinical features distinct from PSP. Our scoring system consists of only five clinical variables that are easily evaluated and efficiently separate BHDS patients from those who have PTX without relying on an imaging study. Further prospective study is needed to confirm our findings. Abstract : The novel scoring system described here readily distinguishes Birt–Hogg–Dubé syndrome (BHDS) from primary spontaneous pneumothorax (PTX) by applying five clinical variables that are easily evaluated, are highly sensitive and have strong specificity. This system provides pulmonologists and thoracic surgeons a tool to avoid overlooking BHDS among the patients with PTX in daily clinical practice.